Gender differences in clinical registration trials: is there a real problem?. (12th February 2018) - Labots, Geert; Jones, Aubrey; de Visser, Saco J.; Rissmann, Robert; Burggraaf, Jacobus
Abstract : Aims: Several studies have reported the under‐representation of women in clinical trials, thereby challenging the external validity of the benefit/risk assessments of launched drugs. Our aim was to determine the extent to which women have been included in clinical trials used for drug registration and to analyse the fraction of women participating in phases I, II and III. Methods: We conducted cross‐sectional, structured research into publicly available registration dossiers of Food and Drug Administration (FDA)‐approved drugs that are prescribed frequently. Furthermore, we analysed compounds with high hepatic clearance and a known gender‐related difference in drug response. In a sensitivity analysis, we compared figures with US disease prevalence data. Results: For 38 of the initial 137 drugs (28%), sufficient data were reported and publicly available. For these drugs, 185 479 trial participants were included, of whom 47% were female and 44% were male; gender was not reported for 9% of participants. However, the number of female participants varied with the phase of the trial, with 22% females in phase I trials vs . 48% and 49%, respectively, in phase II and III trials. When compared with US disease prevalence data, 10 drugs (26%) had a greater than 20% difference between the proportion of females affected with the disease compared with representation in clinical trials. Conclusions: From these publicly available data, there was no evidence of any systematic under‐representation of women in clinical trials.